A Study on Decolorization of Industrial Effluents (International Journal of Innovative Research in Computer Science & Technology, 2022)
Water contamination management is  currently one of main focus areas of the scientific study.  While colored organic molecules typically contribute just  a small percentage of the influent to municipal wastewater,  their hue makes them visually unattractive. Stringent  regulatory procedures are pushing businesses to clean their  wastes effluents to progressively high standards. For  example, as indicated by the quantity of relevant research  publications, pigment removal has recently been a subject  of major scientific interest. Several decolorization  technologies have been published during the previous two  decades, but only a handful have been embraced by  specific industries. Alternative treatments, like biological  and system performed, that are efficient in reducing dyes  or colorants from large volumes of effluents and therefore  are cost effective are needed. This article discusses among  the most widely used, and also most potential,  decolorization processes for industrial effluents. The  decolorizing effectiveness of different causal agents is  studied using a variety of physical, chemical, but also  biological approaches. Furthermore, a critical assessment  of various treatment procedures and emerging technology  is presented, together with comments on their advantages  and disadvantages.
Keywords: Colorants; Dye; Decolorization; Effluents; Technology